E-EDUNOMICS –LIBERTIES IN DEMOCRATIZING THE DIGITAL EDUCATION REVOLUTION - Sanmugam Annamalah; Pradeep Paraman (International Journal of Innovations in Engineering Research and Technology, 2021)
Customers, workers, and employers are all seeing their relationships recast by digital platforms. As a result, adapting to technology rather than simply embracing it has various advantages. Education and competition policies will also have to be changed. Future generations should be provided with the skills they will need to succeed in the developing economy through schools and colleges, while technological democratisation looms, a third wave of democracy is on the horizon. The importance of the Internet in promoting more public activism and government openness has been recognised. We propose the "E-edunomics Triangle" to demonstrate that, while the Internet has democratising impacts, it cannot offer democracy at all levels of society unless technologies are purposefully created for the intricacies of democracy, notably with the involvement of higher educational institutions, governments, and industry in initiating change through technical literacy.